Learning Ecosystems with Educational Monopoly Media - Kusumayanti, Ni Putu Martika; Bayu, Gede Wira (Universitas Pendidikan Ganesha, 2021)
Lack of availability of learning media on ecosystem topics which results in the learning process being less effective. This study aims to describe the prototype of the development of educational monopoly learning media and to produce educational monopoly learning media whose validity has been tested. This type of research is a development research using the ADDIE model which consists of five stages, namely analyze, design, development, implementation, and evaluation. The trial subjects in this study consisted of 2 material experts, 2 media and design experts, 2 practitioners, 3 students for individual trials and 6 students for small group trials. This research data collection method using a questionnaire method with the distribution of a 4 scale rating scale instrument. The data obtained from the assessment results were analyzed using the Mean formula to obtain an average score. The average score of material experts, media experts, design experts, practitioners, individual trials, and small group trials respectively was 3,79, 3,86, 3,78, 3,70, 3,80 with very good qualifications. So that the overall validity of the educational monopoly learning media is in the range of 3.25 <x <4.00 with very good qualifications. Based on this analysis, the educational monopoly learning media on the science content of the ecosystem topic is suitable for use in learning.